2006
DOI: 10.1038/modpathol.3800527
|View full text |Cite
|
Sign up to set email alerts
|

Cell reservoirs in lymph nodes infected with HIV-1 subtype E differ from subtype B: identification by combined in situ polymerase chain reaction and immunohistochemistry

Abstract: In Thailand, the predominant HIV subtype is E, rather than subtype B as in North America and Europe. Subtype E has the ability to replicate in vitro in Langerhans cells. We hypothesized that this cell type might constitute a reservoir for the HIV virus in infected lymph nodes. We examined lymph nodes from 25 HIV-1 subtype E-infected patients to determine the immunophenotype of HIV-1-infected cells, their numbers and their distribution. The presence of HIV was detected either by in situ reverse transcriptase-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Furthermore, although both Tat proteins bind CXCR4 with the same K d , neither is able to induce a transient calcium flux in primary CD4 ϩ T cells (16) or induce CD4 ϩ T cell chemotaxis. 3 In this study, we show that B Tat up-regulates the expression of CXCR4 on the surface of resting CD4 ϩ T cells within 4 h through a dose-and CCR2b-dependent mechanism in a manner similar to CCL2 (42) that does not require de novo protein synthesis but involves the relocation of preexisting CXCR4 to the cell surface combined with a decrease in CXCR4 internalization. However, the mutation found in C Tat renders it unable to bind CCR2b (16) and subsequently unable to up-regulate CXCR4 expression on CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, although both Tat proteins bind CXCR4 with the same K d , neither is able to induce a transient calcium flux in primary CD4 ϩ T cells (16) or induce CD4 ϩ T cell chemotaxis. 3 In this study, we show that B Tat up-regulates the expression of CXCR4 on the surface of resting CD4 ϩ T cells within 4 h through a dose-and CCR2b-dependent mechanism in a manner similar to CCL2 (42) that does not require de novo protein synthesis but involves the relocation of preexisting CXCR4 to the cell surface combined with a decrease in CXCR4 internalization. However, the mutation found in C Tat renders it unable to bind CCR2b (16) and subsequently unable to up-regulate CXCR4 expression on CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 93%
“…Globally, over 50% of all infections are caused by clade C, whereas clade B, the most studied clade, represents just 10% of all infections but is dominant in both Europe and North America. Recent research has shown that the different clades and CRF of HIV-1 have biological differences with respect to transmission (2), replication (3), and disease progression (4,5). Moreover, the HIV-1 proteins gp120 (6), Nef (7,8), Vif, Vpr, Vpu (9,10), and Tat (11)(12)(13)(14)(15)(16)(17)(18)(19) show clade and isotype-specific properties at both the molecular and biological levels.…”
Section: Cxcr4-using Human Immunodeficiency Virus Type 1 (Hiv-mentioning
confidence: 99%
“…Among the defined effects, subtype B Tat has been shown to be chemotactic for monocytes (2,3,50) and microglial cells (26) and to induce the production of tumor necrosis factor (TNF), chemokine (C-C motif) ligand 2 (CCL2) (previously known as monocyte chemotactic protein 1 [MCP-1]), and interleukin-6 (IL-6) from monocytes (25,59,87). However, recent research has shown that the different genetic subtypes and recombinant forms of HIV-1 have biological differences with respect to transmission, replication, and disease progression (14,47,74,85). Moreover, different subtypes of Tat have different in vitro effects (17,18,27,28,57,62,66,67,76).…”
mentioning
confidence: 99%
“…For example, whole HIV-1 virions bound extracellularly to follicular dendritic cells (FDC) in germinal centers (GC) of lymphoid tissues (LT) have been observed [35]. Further still, in those organs associated with extensive lymphoid tissues such as the gut-associate lymphoid tissue (GALT), HIV eradication has been noted to be a challenge [35][36][37][38][39][40][41][42][43][44] regardless of the time-periods of HAART use. Additionally, various recent studies reporting on the genomic compartmentalization of HIV-1 in blood and other organs have also emerged.…”
Section: Current Views On the Sanctuaries And Mechanisms Of Hiv Persimentioning
confidence: 99%
“…Heath et al [51], however, failed to demonstrate similar genetic compartmentalization of HIV-1 between lung and blood. [42][43][44] have used in situ polymerase chain reaction and immunohistochemistry to show that the cell hide-out in lymph nodes infected with HIV-1 subtype E differ from that of subtype B.…”
Section: Current Views On the Sanctuaries And Mechanisms Of Hiv Persimentioning
confidence: 99%